A novel diagnostic method to detect truncated neurofibromin in neurofibromatosis 1. (12th November 2015) - Esposito, Teresa; Piluso, Giulio; Saracino, Dario; Uccello, Rossella; Schettino, Carla; Dato, Clemente; Capaldo, Guglielmo; Giugliano, Teresa; Varriale, Bruno; Paolisso, Giuseppe; Di Iorio, Giuseppe; Melone, Mariarosa A. B.
Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic condition caused by dominant loss‐of‐function mutations of the tumor suppressor gene NF1 that encodes neurofibromin, a negative regulator of RAS activity. Mutation analysis of NF1 located at 17q11.2 has been hampered by the large size of the gene, the high rate of new mutations, the lack of mutational clustering, and the presence of several homologous loci. To date, about 80% of the reported NF1 mutations are predicted to result in protein truncation, but very few studies have correlated the causative NF1 mutation with its effect at the protein level. We evaluated a novel diagnostic method to detect truncated forms of neurofibromin in a large cohort of unrelated subjects suspected of having NF1, according to the NIH consensus criteria. Western blot analysis was carried out on protein extracts from patients' leukocytes to highlight the possible presence of altered neurofibromin as a result of mutations in NF1 . Truncated neurofibromin was identified in 274/336 patients (81%), confirming the usefulness and reproducibility of the proposed diagnostic approach. Our methodology can be routinely applied in the diagnostic setting, thanks to its simplicity and reliability. Combined with molecular approaches, it may increase the accuracy and efficiency of NF1 genetic testing. We evaluated a novel diagnostic method to detect truncated forms of neurofibromin in patients fulfilling the clinical criteria for Neurofibromatosis 1. Western blot analysis identified truncated neurofibromin in 274/336 patients (81%). Our results indicate that the proposed technique is cheap and reliable, and could ideally be performed as a preliminary biochemical screening before molecular analysis of the NF1 gene. Abstract : We evaluated a novel diagnostic method to detect truncated forms of neurofibromin in patients fulfilling the clinical criteria for Neurofibromatosis 1. Western blot analysis identified truncated neurofibromin in 274/336 patients (81%). Our results indicate that the proposed technique is cheap and reliable, and could ideally be performed as a preliminary biochemical screening before molecular analysis of the NF1 gene.